Hardware implementation of PID mode controller for buck converter by using digital signal processing / Pais Saedin, Ahmad Asri Abd Samat and Mohd Najib Mohd Hussain - Saedin, Pais; Abd Samat, Ahmad Asri; Mohd Hussain, Mohd Najib (2011)
Control applications of switched mode power supplies have been widely explored. The focus of this research is to design and controlling the DC-DC Buck converter by using PID controller. The small signal models of the buck converter, obtained using standard state space averaging techniques, was utilized in the project. The PID controller was designed for generic buck converter using standard frequency response techniques. The controller was then transformed into digital controllers. This report presents the simplest method and systematic approach in design a practical Digital Signal Processing (DSP). In this project a Simulink model of the Buck converter is develop and it is controlled by PID controller. The digital controllers designed using linear and nonlinear control methods were implemented on a TI DSP. Experimental and simulation results for the buck were presented and compared.